أبو يعقوب يوسف بن إبراهيم الوارجلاني ودوره في الفكر الإباضي 500 - 570هـ/1100 - 1170م - بن عمارة، أنور, فايزي، أحمد (جامعة الوادي university of Eloued, 2019)
الملخص: ابو يعقوب يوسف بن إبراهيم الوارجلاني ودوره في الفكر الإباضي (500-570هـ /1100-1170 م) إن تعدد القوى في بلاد المغرب الإسلامي واختلاف اتجاهاتها ,ومشاربها الفكرية والثقافية خلق نوعا من ذلك التوازن والاستقرار الحضاري والسياسي,كان هذا بظهور الدولة الرستمية التي كانت في طليعة التنافس في مجال الإنتاج الثقافي والفكري,حيث استطاعت سياسة الأئمة الرستميين في بلاد المغرب الأوسط تحديدا من أن تبني لنفسها ,قاعدة حضارية متينة عاصمتها تيهرت التي تأسست بإعلان قيام الدولة الرستمية سنة 160ه/777 م التي نوه بها أصحاب المصادر والسير في أنها تضاهي باقي الحضارات كالقيروان وقرطبة وسجلماسة وفاس, رغم الاختلاف المذهبي بين دول المغرب الإسلامي إلا أن ذلك لم يكن حائلا دون إقامة جسر من التواصل ,الفكري والثقافي الذي حمله المذهب الإباضي على عاتقه ,والذي قام بدوره المنوط بسبب سياسة الأئمة الرستميين المبنية على حرية الفكر والإنفتاح على الآخر بفضل تلك الملحمة العلمية التي بسطوها. هذه الحضارة ألقت بضلالها على تلك الحواضر المجاورة وخاصة حاضرة وارجلان الضاربة في أعماق صحراء المغرب الأوسط والتي كانت محورا دينيا واقتصاديا لبلاد السودان ومعبرا هاما لركب الحجاج خاصة بعد سقوط العاصمة تيهرت وفرار بعض الأئمة إليها. عرفت وارجلان هذه الفترة حركة علمية كبيرة أفرزت العديد من المشايخ والعلماء ,الذين تركوا آثارهم في شتى المجالات والميادين الفكرية والكلامية والعقدية والتاريخية,خاصة داخل المذهب الإباضي ومن أهم روادها ابو يعقوب يوسف بن إبراهيم الوارجلاني,المتوفى سنة 570ه/1170م الذي يعد من أعمدة مصادر التشريع الإباضي نضير ما تركه من مؤلفات عديدة وآراء عقدية وأصولية منها في الاصول كان (العدل والإنصاف في معرفة أصول الفقه والاختلاف) في ثلاثة أجزاء وقد ورد ذكره في العديد من كتب السير الإباضية,حيث اعتمد أبو يعقوب في منهجه على القواعد الأصولية التي استوعبها من الذين سبقوه , ايضا في علم الكلام والعقيدة مؤلفه الذي يعد مصدرا اساسيا للمذهب الاباضي لما حمله من عديد الاراء الكلامية وهو( الدليل لأهل العقول لباغي السبيل بنور الدليل وتحقيق مذهب الحق بالبرهان والصدق), اما في علم الفلسفة فكان كتابه مرج البحرين , كما كان ابو يعقوب محدثا عن طريق مؤلفه ترتيب مسند الربيع بن حبيب (الجامع الصحيح) ومفسرا بسفره الكبير الذي تركه كما ذكر ذلك البرادي الذي يحوي سبع مائة ورقة , كما كان ابو يعقوب ايضا مؤرخا بكتابه (فتوح المغرب), اضافة الى تضلعه في الادب والشعر بتركه قصيدته الحجازية التي نسج فيها ثلاث مائة وثمانون بيتا واصفا فيها رحلته الى بلاد المشرق ورحلته الى الحج ,ايضا قصيدته البائية التي رثى فيها شيخه أبا ايوب بن اسماعيل . ومن خلال هذه الدراسة يمكن ان نستخلص النتائج التالية : - إن سياسة الشدة والاستبداد والتهميش التي مورست ضد البربر, من طرف بعض حكام بني أمية ساهمت بشكل كبير في ردة فعل سكان البربر, وثورتهم ضد النظام السائد بتبني الأفكار التي تخدم مصالحهم ومنها الفكر الإباضي. - دور حملة العلم الخمسة في تهئة تلك الأرضية الخصبة ,بحرثها من اجل بذرها بواسطة السفر لنهل العلوم على يد أبي كريمة, وبواسطة سلمة بن سعد والعودة لنشر تلك الأفكار الإباضية, بين أوساط قبائلهم التواقة لكل ماهو بديل. - قيام الكيان السياسي للدولة الإباضية المتمثل في الدولة الرستمية,وعاصمتها تيهرت التي اتخذت من مبدأ الشورى والعدل أساس الحكم ,و نظام حياة لا يفرق بين العربي والبربري ولا الأعجمي, إلا بالعلم والكفاءة هذا الأمر سرع من وتيرة تطورها . - تبني الحكام الرستميين سياسة تشجيع العلم والعلماء والمجالس العلمية والمناظرات,وتشجيع الحركة العلمية بكل ما تحويه من معنى ,من بناء للمكتبات والمساجد جعلها محجا ومقصدا للعديد من أهل العلم ,ومنها الى باقي الحواضر المجاورة كوارجلان. - ظهور حاضرة وارجلان كحاضنة للعلم والعلماء, وأهل الفقه بعد سقوط العاصمة تيهرت ,بحكم موقعها الاستراتيجي في صحراء المغرب الأوسط التجاري, ومسلكا من مسالك ركب الحجاج الى الحجاز,هذا الأمر جعلها ملجأ لعلماء المذهب الإباضي, الذين قصدوها لإحياء الحركة العلمية من جديد نضرا لاستقرارها. - الحركة العلمية بوارجلان ولدت العديد من العلماء ,وكان من أبناء هذه المنطقة ابو يعقوب يوسف الوارجلاني الذي فاق علمه أقرانه, ومن عاصره بفضل نباهة عقله وقدرته على الإستيعاب. - دور الرحلة في تطوير الذات واكتساب العلوم وعملية الاسترزاق ,واكتشاف المناطق وهو ما قام به ابو يعقوب في طلبه لتلك الاستزادة ,في رحلة سودانية تجارية أندلسية علمية ثم حجازية دينية. - دراسة ابو يعقوب الأنثروبولوجية و الطبونيمية الدقيقة، للطرق التي سلكها و يمكن أن نصنفها ضمن كتب المسالك والممالك،لما حوته من توصيف دقيق فقد اطلعنا على الصحاري والقبائل في طريقه ونقده لبعض التصرفات كظاهرة المكس - اكتشافه لبلاد السودان ,ووصوله خط الاستواء . - عملية الاحتكاك بالعلماء تظهر تبني أفكارهم أو نقدها ,وهذا ما كان لأبي يعقوب الذي تبنى الأفكار الكلامية الفلسفية المرتبطة أساسا بالعقيدة مقيما الحجة والدليل ,على خصومه بالعلم والمعرفة والأدلة العقلية والنقلية. - العلم عند ابو يعقوب ثلاثة : علم ضروري وعلم نظري وعلم لدني . - يعتبر كتاب الدليل والبرهان ﻣﻦ ﺃﻫﱢﻢ ﻣﺼﺎﺩﺭ ﺍﻟﻌﻘﻴﺪﺓ ﻋﻨﺪ ﺍﻹﺑﺎﺿﱠﻴﺔ، ﻭﺑﻌﺘﱪ ﺃﻳﻀﺎ ﻣﻦ أهم ﺍﻟﻜﺘـﺐ ﺍالكلامية ﻋﻨﺪﻫﻢ لما يحويه من فكر وآراء لأبي يعقوب كقضية خلق القران, التي لم يرد الوارجلاني الخوض فيها وان القرآن مجعولا منزلا,والكفر عنده كفر نعمة وكفر جحود وكفر أفعال. - يتفق أبو يعقوب ﻣﻊ ﺍﳌﻌﺘﺰﻟﺔ ﺍﻟﱵ ﺗﻘﻮﻝ :أن ﺍﻟﻌﻠﻢ ﺑﺎﷲ ﻭﺍﻹﳝﺎﻥ ﺑﻪ ﻳﻨﺎﻝ ﻣﻦ ﺟﻬـﺔ ﺍﻟﻔﻜﺮ - يعتبر كتاب العدل والإنصاف للوارجلاني مثالا لتداخل علم الأصول بعلم الكلام نظرا لاشتغاله بعلم الكلام ما أثر على الترجيح الأصولي. - اشتغال ابو يعقوب الوارجلاني بعلم التنجيم,كظاهرة كانت سائدة في عصره - وأخيرا بينت لنا هذه الدراسة عن مدى الحرص والاجتهاد لأبي يعقوب يوسف الوارجلاني , مما يبن انه قوي الحجة وواسع المعرفة والأفق , ذو نظرة ثاقبة دقيقة فتح بذلك أبوابا كثيرة للعلم والعلماء للمضي قدما في خدمة الفكر والمذهب الإباضي . وبهذا البحث نكون قد ساهمنا بوضع لبنة من اللبنات التي تنفض الغبار على التراث والموروث الثقافي الإباضي, الذي لم يلق الدراسة الكافية وخاصة في البحث في مخطوطاته المركونة بين ادراج الخزائن. ملخــــــــص البحث باللغة الانجليزية Abu Ya'qub Yusuf ibn Ibrahim al-Warajlani And his role in Ibadi thought (500-570h / 1100-1170 m) The multiplicity of powers in the Islamic Maghreb and its different orientations, and its intellectual and cultural stratagems created a kind of balance and cultural and political stability. This was the emergence of the Rustamist state, which was at the forefront of competition in the field of cultural and intellectual production. Which is founded by the declaration of the establishment of the Rustamite state in 160 AH / 777 CE, which was noted by the owners of the sources and walk in that it is comparable to other civilizations such as Kairouan, Córdoba, Segmassa and Fez, despite the doctrinal differences between the Islamic Maghreb countries, but this did not happen. Were prevented from establishing a bridge of communication, intellectual and cultural, which was carried by the Ibadi doctrine on its shoulders, which was due to the policy of the Rustomist imams based on freedom of thought and openness to the other thanks to the scientific saga that they spread. This civilization shed its shadow on those neighboring cities, especially the capital and the two legged tribes in the deep desert of the Middle Maghreb, which was a religious and economic hub for the country of Sudan and an important way to ride pilgrims, especially after the fall of the capital Tehert and the escape of some imams. This was a period of great scientific activity which resulted in many sheikhs and scholars who left their traces in various fields and fields of thought, speech, history and history, especially within the Ibadi sect. The most prominent of its pioneers was Abu Ya'qub Yusuf ibn Ibrahim al-Warajlani, who died in 570 AH / 1170 AD Ibadi Nadeer left many of the writings and opinions of the fundamentals and fundamentalism in the assets was (fairness and fairness in the knowledge of the origins of jurisprudence and difference) in three parts has been mentioned in many books of the Ibadi, where he adopted Abu Jacob in his approach to the fundamentalist rules absorbed by those who preceded , Also in the science of speech and doctrine, which is a major source of the doctrine of Abadi, which carried a number of words of speech (a guide to the minds of the ignorant of the path of light proof and the realization of the doctrine of truth and proof of truth), either in philosophy was his book Marj Bahrain, as was Abu Jacob The author of the book, Musnad al-Rabee'a ibn Habib (the correct mosque), explained his great travel which he had left, as mentioned by al-Baradi, which contains seven hundred leaves. Abu Ya'qub was also a historian of his book Fattouh Morocco, in addition to his poetry and poetry, Three hundred eighty-five houses describing his trip to B Ladd Mashreq and his journey to the Hajj, also his poem Baiith in which his sheikh Aba Ayoub bin Ismail was deplored. In this study we can draw the following conclusions: - The policy of distress and tyranny and marginalization practiced against the Berbers, by some rulers of illiteracy contributed significantly to the reaction of the Berber population, and their revolution against the prevailing system by adopting ideas that serve their interests, including Ebadi thought. - The role of the five science campaign in preparing this fertile ground, plowing it for sowing through the travel of science by Abu Karima, and by Salma bin Saad and the return of the dissemination of Ibadhi ideas, among their tribes eager for each alternative. - The establishment of the political entity of the Ibadi state represented by the Rustist state, with its capital, Teherat, which adopted the principle of consultation and justice as the basis of government, and a system of life that does not differentiate between the Arab, Berber and Ajami. - The rulers of Rustamite adopted the policy of encouraging science, scientists, scientific councils and debates, and to encourage the scientific movement with all its meaning, from building libraries and mosques to make it a mosque and a destination for many scholars, including to the neighboring cities of Quarglan. - The emergence of the city and the feet as an incubator of science and scientists, and the people of jurisprudence after the fall of the capital Tehert, by virtue of its strategic location in the desert of Morocco's commercial center, and the course of the paths of pilgrims to the Hijaz, which made it a refuge for the scholars of the Ibadi doctrine, who intended to revive the scientific movement again for the freshness of stability. - Scientific movement Buarglan was born many scientists, and was a member of this region, Abu Yacoub Yousuf al-Warljani, whose knowledge exceeded his peers, and his contemporaries thanks to the purity of his mind and ability to absorb. - The role of the journey in self-development, acquisition of science and the process of estrangement, and the discovery of areas, which was done by Abu Yacoub in his request for this increase, on a journey of Sudanese commercial Andalusian scientific and religious Hijaz. - The study of Abu Yaqoub Anthropological and Tmonimime minute, for the methods he took and can be classified within the books of the tracts and kingdoms, because of his characterization of accurate We have seen the deserts and tribes in his way and criticism of some behaviors such as the phenomenon of - His discovery of the country of Sudan, and the arrival of the equator. - The process of friction with scientists shows the adoption of their ideas or criticism, and this was the father of Jacob, who adopted the ideas of philosophical words associated with the doctrine of the basis of argument and evidence, the opponents of science and knowledge and evidence of mental and mobility. - The science of Abu Yacoub three: necessary science and theoretical science and secular science. The book of evidence and evidence is considered one of the most important sources of faith in Abadiyya. It is also considered one of the most important books in their writings, because it contains the thoughts and opinions of Abu Yacoub as the cause of the creation of the Qur'an, which the Arjalani did not want to dwell on. - Abu Yaqoub agrees with the Mu'tazilah, which says: The knowledge of God and belief in him gets from the point of view - The book of justice and fairness of Varglani is an example of the overlap of the science of assets with the science of speech because of his work with the science of speech, which influenced the weighting of the fundamentalist. - The work of Abu Yaqub al-Warljani astrology, as a phenomenon that prevailed in his time Finally, this study showed us the diligence and diligence of Abu Yacoub Yousef Al-Wergalani, which is built as a strong argument and broad knowledge and horizons, with an insightful insight that opened many doors for science and scientists to move forward in the service of Ibadi thought and doctrine. In this research we have contributed to the development of a brick of dust-proof buildings on the heritage and cultural heritage Ibadi, which has not received sufficient study, especially in the search of manuscripts stored between the inclusion of safes.
مذكرة ماستر في التاريخ تخصص تاريخ المغرب الإسلامي في العصر الوسيط
Keywords: أبو يعقوب يوسف بن ابراهيم الوارجلاني; Abou Yacoub Yousef bin Ibrahim Allowargelana